PREVALENCE OF WORK-RELATED MUSCULOSKELETAL DISORDERS AMONG LABORATORY WORKERS. - Syed Murtaza Ali1 Mahak Memon2, ,Zunaira 3, Archina 4, Irum 5, Asma 6, Marish Memon7, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
OBJECTIVES: To determine the prevalence of Work-Related Musculoskeletal Disorders among laboratory workers. METHODOLOGY: This cross-sectional study design was used from November 2019 to January 2020, among randomly selected laboratory workers. Data was collected using standardized Nordic Musculoskeletal Questionnaire (SNMQ) andNumericPain Rating Scale (NPRS) to determinethe prevalence of Work-Related Musculoskeletal Symptoms and pain intensity along with participants’ demographic data, among laboratory workers. Data was analyzed using the Statistical Package for the Social sciences (SPSS) version 20 and summarized by descriptive statics, which were presented using frequency tables and expressed as percentages, mean+SD. RESULTS: In this study we found 38% prevalence of Work Related Musculoskeletal Disorders (WRMSDs) among laboratory workers. Moreover, ankles/feet turned out to be the most symptomatic region with prevalence of 0.7% followed by neck and upper back being more common among male 131(87.3%), laboratory technicians 121(81.3%), with mean age of 34.65(11.82%). In our study, most of the participants (63.3%) were having mild pain and 4% had severe pain. CONCLUSION: In conclusion, high prevalence of Work-Related Musculoskeletal Pain, affecting one or both ankles/feet, neck, and upper back. Most of the study participants reported having mild pain